2013
DOI: 10.1186/1476-069x-12-64
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic load amplifies the effect of blood lead levels on elevated blood pressure among middle-aged U.S. adults: a cross-sectional study

Abstract: BackgroundScientists and regulators have sought to understand whether and how physiologic dysregulation due to chronic stress exposure may enhance vulnerability to the adverse health effects of toxicant exposures. We conducted a cross-sectional study to determine whether allostatic load (AL), a composite measure of physiologic response to chronic exposure to stress, amplifies the effect of lead exposure on blood pressure among middle-aged adults.MethodsWe analyzed associations between blood lead levels and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
1
33
0
1
Order By: Relevance
“…Of these 12 references, three did not use NHANES data and one was included in our original search. Therefore, this review on the calculation of ALS is based on 21 studies which used NHANES data in surveys of various lengths of time between 1988 and 2010[323]. …”
Section: Perspectivementioning
confidence: 99%
“…Of these 12 references, three did not use NHANES data and one was included in our original search. Therefore, this review on the calculation of ALS is based on 21 studies which used NHANES data in surveys of various lengths of time between 1988 and 2010[323]. …”
Section: Perspectivementioning
confidence: 99%
“…A cross-sectional analysis of NHANES data by Zota et al reported that higher allostatic load (used as a proxy measure of stress, and assessed using a 7-item composite of indicators of cardiometabolic dysregulation) heightened associations between blood Pb and blood pressure [23]. In a longitudinal cohort of older adults in Baltimore, Maryland, Glass et al found heightened effects of bone Pb on cognitive function with greater exposures to self-identified neighborhood psychosocial stressors [43].…”
Section: Epidemiologic Evidence For Effect Modification By Stress/strmentioning
confidence: 99%
“…As a result, they may be capturing downstream effects of perceived stress, rather that solely reflecting its occurrence per se. Thus, it remains a topic of some debate as to whether allostatic load, often measured using a composite of cardiometabolic risk factors including CRP, high-density lipoprotein cholesterol, serum triglycerides, and waist-hip circumference [12,23], is indeed an appropriate proxy measure of chronic stress, or rather downstream effects. Given this uncertainty, findings in studies that use allostatic load as a marker of stress per se should be interpreted with some caution.…”
Section: Background: Chronic Stress and Stress Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between race/ethnicity, socioeconomic status, and allostatic load have been established (25,56). Allostatic load may also amplify the adverse effects of environmental chemical exposures, such as lead exposure on risk of hypertension among adults and the effect of housing quality on asthma risk in children (27,49,55,77).…”
Section: Allostatic Loadmentioning
confidence: 99%